Competitiveness and Determinants of Coffee Exports, Producer Price and Production for Ethiopia - Boansi, David; Crentsil, Christian (Journal of Advanced Research in Economics and International Business; Vol 1 No 1 (2013): JAREIB Volume I Issue 1 Summer 2013, 2013)
This study analyzed the performance and determinants of coffee exports, producer price and production for Ethiopia. The Revealed Comparative Advantage and Revealed Symmetric Comparative Advantage measures of competitiveness used for the performance analysis show that even though Ethiopia has comparative advantage in export of coffee, the same cannot be said of its overall performance on the international market owing to challenges with management of price risk, high transaction cost resulting from the extensive nature of the supply chain and the numerous actors and processes therein, challenges with quality control, low productivity of growers’ fields, and incidence of smuggling. To improve upon its export performance and ensure continuous growth in its exports, prices and production, we propose investment in yield-enhancing innovations, devising and implementation of measures to improve quality control in the supply chain, address issues with price risk, minimize incidence of smuggling, minimize transaction costs, increase and ensure continuous government support to the subsector, hold onto the current devaluation of the Ethiopian birr, ensure payment of fair prices to growers and appropriately transmit future increments, increase current area under cultivation to enhance efficient utilization of the abundant labor, and to attract more export-oriented foreign direct investments (to enhance trade creation).